Penerapan Sistem Informasi Berbasis Web Untuk Pengelolaan dan Pengarsipan Dokumen - Reni Kurniah (Infotek: Jurnal Informatika dan Teknologi, 2023)
The web-based document archiving information system is an information system that is useful for managing archive storage where the information system created will assist in the process of storing and managing documents. Dr. Hazairin in order to improve the quality of the document archiving process, a web-based document archiving information system was designed, in order to avoid damage and also reduce the storage space for archives and the process of searching for archives can be done anywhere. The document archiving information system was created using the codeinether framework while the method stages carried out in this research process started from field studies, literature studies, interviews, system design and software where at this stage the database design system was used using MySQL, then system implementation and testing and the final stage is system integration and testing. After system integration and testing, the system can be applied to universities where access rights to the system will be divided into 7 parts, namely rectorate access requirements, faculty access requirements, institutional access requirements, bureau access requirements, study program access requirements, unit access requirements, and access requirements super admin